Эмнэлгийн рентген төхөөрөмжийн цацрагийн хамгаалалтын тооцоолол - tsengel, ganzul; M, Odsuren; Д, Болортуяа (Scientific transaction of the National University of Mongolia. Physics, 2024)
In this study, we performed radiation shielding calculations for the diagnostic X-ray equipment at Rekha Med Hospital. The lead thickness required for radiation protection, as determined by the methodology outlined in the National Council on Radiation Protection and Measurements (NCRP) Report No. 147, was approximately 2 mm. Air kerma measurements were taken outside the X-ray room to validate the shielding effectiveness with a 2 mm thick lead barrier installed along the walls. The results confirmed that the air kerma dose did not exceed the regulatory dose limit of 0.5 mSv/H in uncontrolled areas, indicating sufficient shielding.